KONSEP KEADILAN GENDER DALAM PUTUSAN VERSTEK PADA CERAI GUGAT DI MAHKAMAH SYAR’IYAH LANGSA DALAM BINGKAI HUKUM KELUARGA ISLAM - Ulya, Nur Afina (JURNAL HAKAM, 2023)
The concept of gender justice is an essential thing that must be applied to various aspects of life, especially in the realm of religious courts. Justice that must be enforced means the fulfillment of the rights of men and women fairly without causing various forms of discrimination. The absence of the husband as the defendant in a divorce case in court will cause problems in the examination of the case and harm the rights of the wife as the plaintiff. The absence of the defendant in court or not presenting his representative will impact the decision, so it must be decided in a verstek manner. In writing using a gender approach and Islamic family law. The research found that the verstek decision was categorized as an effort to protect the wife's rights as a plaintiff. This study uses a descriptive qualitative method in analyzing the data of the three decisions and the results of the interviews. As for interviews as reinforcing data in the analysis of decisions conducted with three judges in studying the objectivity of law in the experience and knowledge of judges in the decision. The results of this study are that women's rights have been fulfilled with all legal considerations by judges who are correct and in line with the concept of Islamic family law.